Computation of Channel Capacity Based on Self-Concordant Functions - Da-gang Tian; Yi-qun Huang (Journal of Electrical and Computer Engineering)
The computation of channel capacity is a classical issue in information theory. We prove that algorithms based on self-concordant functions can be used to deal with such issues, especially when constrains are included. A new algorithm to compute the channel capacity per unit cost is proposed. The same view is suited to the computation of maximum entropy. All the algorithms are of polynomial time.